+0  
 
0
52
1
avatar+4407 

Help

NotSoSmart  Nov 21, 2018
 #1
avatar+92787 
+1

Not the first one 

(3x^2 - y)^2    =  (3x^2 - y) (3x^2 - y)  = 9x^4 - 3x^2y - 3x^2 + y^4 =

9x^4 - 6x^2 + y^4

 

Second one      (3x^2)^2 - y^2   =  9x^4 - y^2

 

Third one  9(x^2)^2 - y^2   = 9x^4 - y^2

 

Not the fourth one   (9x^2)^2 - y^2   = 81x^4 - y^2

 

Fifth one    (3x^2 + y) (3x^2 - y)   = 9x^4 +3x^2y - 3x^2y - y^2   = 9x^4 - y^2

 

So......First, Third, Fifth

 

cool cool cool

CPhill  Nov 21, 2018

3 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.